Fifty three new record species of benthic diatoms from mekong river and its tributaries in Thailand - Suphan S. (2014)
A study on the diversity of benthic diatoms in Mekong River and its tributaries in Thailand was carried out during July 2005 to April 2007. Two hundred and fifty three species of benthic diatoms were found. Fifty three species have never been previously recorded in Thailand. It could be classified into 3 classes, 11 orders, 22 families and 32 genera. The detailed descriptions of these new records were reported.